2015
DOI: 10.1039/c4ta05186f
|View full text |Cite
|
Sign up to set email alerts
|

High-performance lithium iron phosphate with phosphorus-doped carbon layers for lithium ion batteries

Abstract: A novel composite of LiFePO 4 with phosphorus-doped carbon layers has been prepared via a simple hydrothermal method using glucose as the carbon source to generate the carbon coating and triphenylphosphine as the phosphorus source. Effects of phosphorus doping on the phase purity, morphology and electrochemical performance of the materials are studied by the characterizations of Xray diffraction, Raman spectra, scanning electron microscopy, high resolution transmission electron 10 microscopy and electrochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(36 citation statements)
references
References 43 publications
2
34
0
Order By: Relevance
“…As expected, two peaks at 132.9 eV and 130.4 eV appeared after phosphorus doping which could be associated to characteristic peaks of P-O and P-C bonding, respectively35,36 . It exhibits typical amorphous carbon structure with peaks at around 25° and 43° corresponding to the (002) and (100) planes of graphite.…”
supporting
confidence: 74%
“…As expected, two peaks at 132.9 eV and 130.4 eV appeared after phosphorus doping which could be associated to characteristic peaks of P-O and P-C bonding, respectively35,36 . It exhibits typical amorphous carbon structure with peaks at around 25° and 43° corresponding to the (002) and (100) planes of graphite.…”
supporting
confidence: 74%
“…These were then successfully applied to the existing commercial LiFePO 4 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 type co-doped carbon coating on the material can generate the synergistic effect to elevate the high-rate capacity much higher than the sum of single doping. This is attributed to the electron-type and the hole-type carrier donated by nitrogen and boron atoms.…”
Section: Discussionmentioning
confidence: 99%
“…Conductive surface modifications towards carbon coating of olivine-structured lithium iron phosphate (LiFePO 4 ) have attracted significant attention due to its high-efficiency and environmental benign in the development of lithium ion battery cathode materials [1][2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…LiFePO 4 nanoparticles prepared by a facile solvothermal process with water/N-methyl-2-pyrrolidone (NMP) solvent system exhibit excellent electrochemical performance [11]. In addition, LiFePO 4 /NiP nanospheres prepared using a spraying technique has a high electronic conductivity [12]. It was also reported that surface modifications by carbon coating and atomic-level doping with alien ions are effective to improve the electronic conductivity [13].…”
Section: Introductionmentioning
confidence: 97%